Potentiation of the Antithrombotic Action of Dermatan Sulphate by Small Amounts of Heparin - Thomas, D P; Gray, E; Merton, R E (Thrombosis and Haemostasis, 1990)
We have examined the effect in impairing thrombus formation of a preparation of dermatan sulphate (DS) alone and DS plus small amounts of unfractionated heparin (UFH). In rabbits given a dose of 150 μg/kg of DS alone, there was minimal reduction in serum-induced stasis thrombosis (Wessler model), with an overall score of 92.5% (100% = no impairment of thrombus formation). When the same dose of DS containing UFH was given (two different subgroups given DS containing 0.25 and 2.5% heparin by dry weight, respectively), the overall thrombus score was reduced to 60% (P <0.003), with no significant difference between the two subgroups. To achieve a comparable result with DS alone, a dose of 1 mg/kg was required. We conclude that very small amounts of UFH significantly enhance the antithrombotic action of DS, by a mechanism that has yet to be determined.